Impact of rearing temperature on the innate antiviral immune response of growth hormone transgenic female triploid Atlantic salmon (Salmo salar). Issue 97 (February 2020) - Ignatz, Eric H.; Braden, Laura M.; Benfey, Tillmann J.; Caballero-Solares, Albert; Hori, Tiago S.; Runighan, C. Dawn; Fast, Mark D.; Westcott, Jillian D.; Rise, Matthew L.
Abstract: AquAdvantage Salmon (growth hormone transgenic female triploid Atlantic salmon) are a faster-growing alternative to conventional farmed diploid Atlantic salmon. To investigate optimal rearing conditions for their commercial production, a laboratory study was conducted in a freshwater recirculating aquaculture system (RAS) to examine the effect of rearing temperature (10.5 °C, 13.5 °C, 16.5 °C) on their antiviral immune and stress responses. When each temperature treatment group reached an average weight of 800 g, a subset of fish were intraperitoneally injected with either polyriboinosinic polyribocytidylic acid (pIC, a viral mimic) or an equal volume of sterile phosphate-buffered saline (PBS). Blood and head kidney samples were collected before injection and 6, 24 and 48 h post-injection (hpi). Transcript abundance of 7 antiviral biomarker genes ( tlr3, lgp2, stat1b, isg15a, rsad2, mxb, ifng ) was measured by real-time quantitative polymerase chain reaction (qPCR) on head kidney RNA samples. Plasma cortisol levels from blood samples collected pre-injection and from pIC and PBS groups at 24 hpi were quantified by ELISA. While rearing temperature and treatment did not significantly affect circulating cortisol, all genes tested were significantly upregulated by pIC at all three temperatures (except for tlr3, which was only upregulated in the 10.5 °C treatment). Target gene activation was generally observed at 24 hpi, with most transcript levels decreasing by 48 hpi in pIC-injected fish. Although a high amount of biological variability in response to pIC was evident across all treatments, rearing temperature significantly influenced transcript abundance and/or fold-changes comparing time- and temperature-matched pIC- and PBS-injected fish for several genes ( tlr3, lgp2, stat1b, isg15a, rsad2 and ifng ) at 24 hpi. As an example, significantly higher fold-changes of rsad2, isg15a and ifng were found in fish reared at 10.5 °C when compared to 16.5 °C. Multivariate analysis confirmed that rearing temperature modulated antiviral immune response. The present experiment provides novel insight into the relationship between rearing temperature and innate antiviral immune response in AquAdvantage Salmon. Highlights: Injection of pIC activates most targeted antiviral biomarker genes by 24 hpi. Rearing temperature affects AquAdvantage Salmon's antiviral immune response. Differential pIC-responsive expression observed in tlr3, lgp2, stat1b, isg15a, rsad2 and ifng due to temperature. Plasma cortisol was not affected by injection treatment or rearing temperature.